2023
DOI: 10.1002/jgh3.12963
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of gout in patients with inflammatory bowel disease: A population‐based study

Osama Hamid,
Khaled Alsabbagh Alchirazi,
Ahmed Eltelbany
et al.

Abstract: Background and AimArthritis is a recognized extra‐intestinal manifestation of inflammatory bowel disease (IBD). Studies show altered uric acid metabolism in IBD. This study aims to investigate the association between IBD and gout.MethodsWe used a multi‐center database (Explorys Inc.) consisting of data from several US healthcare systems. We identified adults diagnosed with Crohn's disease (CD) and ulcerative colitis (UC) between 1999 and 2022. In this cohort, we identified patients diagnosed with gout. We coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…Additional file 4 : Table S3 displays the lower aHR of colorectal cancer for the colchicine users among the chronic colitis-(ulcerative colitis, Crohn’s disease) in young adult [ 9 , 18 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional file 4 : Table S3 displays the lower aHR of colorectal cancer for the colchicine users among the chronic colitis-(ulcerative colitis, Crohn’s disease) in young adult [ 9 , 18 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Hamid et al report that out of the 69,260,780 patients in the database, they identified 209, 020 patients with ulcerative colitis (0.30%) of whom 9130 had gout (4.3%). Additionally, 249,480 had Crohn’s disease (0.36%) of whom 14,000 had gout (5.61%) [ 33 ], such that, the number of the gout with IMIDs-chronic colitis is 9130 + 14,000 = 23,130. We assumed the 75% gout patients with colchicine use, the number of colchicine user is about (23,130) × 0.75 = 17,348.…”
Section: Discussionmentioning
confidence: 99%